Free vibration analysis of delaminated beam with two surface cracks - Ho, Jim Zhow. (2013)
In the modern world, there is an increase demand in the usage of beams in the engineering industry. Compsite beam are mainly used in the manufacturing of aerospace, marine and civil structure and machinery because of their exceptional mechanical properties such as strength and stiffness.